Touch Thee Not: Group Conflict, Caste Power, and Untouchability in Rural India - Indraneel Dasgupta; Sarmistha Pal (Institute of Labor Economics (IZA), 2018)
We investigate the impact of community power on the practice of untouchability in rural India. We model two-dimensional simultaneous group conflict over social norms, wherein an upper and backward (OBC) caste Hindu bloc contests the 'scheduled' castes (SCs) over the extent to which behavioural norms within the village should legitimise untouchability, even as it seeks to impose Hindu values/rituals on non-Hindus. We find that any increase in the collective resource endowment (power) of this bloc will increase the likelihood of an upper caste or OBC Hindu household practising untouchability. An increase in that of SCs, or, more interestingly, of Muslims and Christians, will reduce it. Strikingly, a marginal redistribution of resources from OBCs to upper castes may reduce it as well. Identifying a community's power with a multiplicative combination of its population share and land share, we find support for these hypotheses in data from the India Human Development Survey 2011-12.
Keywords: D72; D74; J71; J78; Z1; 330; caste; social norm; ritual purity; discrimination; untouchabilitly; land redistribution; caste power; India